A CINEMA UNDER THE STARS (AND STRIPES): DAVID MILGRAM'S BOULEVARD DRIVE-IN THEATRE AND THE POLITICAL-ECONOMIC LANDSCAPE OF AMERICA'S POST-WAR DRIVE-IN BOOM. Issue 2 (2nd April 2020) - Phillips, W. D.
Abstract : The sudden proliferation of drive-in theatres in America following World War II has long been attributed to the urban exodus to the suburbs and the growth of car culture. Looking closely at David Milgram's Boulevard Drive-in Theatre in Allentown, Pennsylvania, and his legal quest for first-run programming, this article offers a supplementary history of the political-economic landscape of the period. The result is a more complete understanding of the historical forces behind the drive-in and its sudden rise to significance. Characterised by Congressional industry-friendly laws and allocations that quietly dismantled the commercial model of the 'whirlpool' city, this era simultaneously witnessed a reformulation of the film industry's long-standing exhibition model. Hollywood exhibition, supporting and supported by vertical integration, was also built on such a conceptualisation of urban organisation. After the war, however, film exhibition was taken away from the Hollywood studios by a law-interpreting judiciary that was the political obverse of their law-making contemporaries. The American drive-in movie theatre and entrepreneurs such as Milgram that drove its post-war boom were the inadvertent beneficiaries of this unique post-war political-economic dynamic that opened up a space for them in both America's cities and its motion picture industry.